2020
DOI: 10.2196/17955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web-Based Patient Portal on Patient Satisfaction and Missed Appointment Rates: Survey Study

Abstract: Background Although electronic medical record (EMR)-tethered patient portals are common in other countries, they are still emerging in Canada. Objective We aimed to report user satisfaction and the effects of a patient portal on medical appointment attendance in a Canadian cohort of patients within our publicly funded health care system. Methods Two surveys were deployed, via email, at 2 weeks and 6 months f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 16 publications
12
55
0
Order By: Relevance
“…In this study, we sought to clarify why portals can, at times, fail to achieve their transformative potential. In parallel with this work, a quantitative survey was conducted on patient views of the portal [ 12 ], and the views of the clinicians and managers presented here complement those findings.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we sought to clarify why portals can, at times, fail to achieve their transformative potential. In parallel with this work, a quantitative survey was conducted on patient views of the portal [ 12 ], and the views of the clinicians and managers presented here complement those findings.…”
Section: Introductionmentioning
confidence: 99%
“…The following sections summarize the studies according to the QA dimensions ( Multimedia Appendices 3 - 6 ) [ 27 , 43 , 44 , 46 - 48 , 53 , 55 - 58 , 60 - 63 , 65 , 67 , 68 , 72 - 103 , 105 - 114 , 119 , 126 , 127 , 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…The patient perspective was explored in 44 peer-reviewed [ 43 , 44 , 46 - 48 , 53 , 55 , 56 , 58 , 60 - 63 , 65 , 67 , 68 , 72 - 99 ] and 15 gray literature [ 100 - 114 ] studies. Several methods (mixed, n=12; observational, n=5; qualitative, n=5; RCT, n=1; retrospective, n=14; and survey, n=22) were applied to gain insights from patients through surveys, interviews, focus groups, and administrative data.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, one of the included studies in this review suggested that actions related to portal use, such as checking a test result, can increase office visits, while actions, such as repeat prescription ordering during the after-hours period, might reduce hospitalizations [ 34 ]. A recent survey study of a patient portal with access to health care records, test results, e-messaging, and appointment booking reported that patients believed portal use helped them “avoid a clinic visit” [ 39 ]. Few studies in the literature also examined the association between patient portal use and missing medical appointments [ 39 , 40 ], which was not examined in any of the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey study of a patient portal with access to health care records, test results, e-messaging, and appointment booking reported that patients believed portal use helped them “avoid a clinic visit” [ 39 ]. Few studies in the literature also examined the association between patient portal use and missing medical appointments [ 39 , 40 ], which was not examined in any of the studies included in this review. The health care utilization outcomes associated with patient portal use may need further investigation as the number of studies examining these associations is limited.…”
Section: Discussionmentioning
confidence: 99%